Original paperAssociation of methylenetetrahydrofolate reductase gene polymorphisms with basal cell carcinoma development - Wódz-Naskiewicz, Karolina; Narbutt, Joanna; Rogowski-Tylman, Michał; Pawliczak, Rafał; Sobjanek, Michał; Sysa-Jędrzejowska, Anna; Włodarkiewicz, Adam; Lesiak, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Basal cell carcinomas (BCCs) are the most common cancers occurring among Caucasians. The main risk factors for development of BCC is excessive exposure to ultraviolet radiation, especially UVB, which simultaneously leads to DNA damage in keratinocytes. The genetic background of BCC includes multiple genes including the gene encoding methylenetetrahydrofolate reductase (MTHFR), which is a critical enzyme in folate metabolism and DNA repair. Aim : To assess the frequency of 665C/T (rs1801133) and 1286A/C (rs1801131) polymorphisms in the MTHFR gene in patients with BCC. Material and methods : The study comprised 142 patients with BCC and 142 healthy volunteers matched for age and sex as a control group. Presence of the two studied polymorphisms was assessed by PCR-RFLP. Results : CT genotype in MTHFR 665C/T polymorphism and CC genotype in 1286A/C significantly increases the risk of BCC (OR = 3.39, p = 0.00008 and OR = 4.240, p = 0.032; respectively). Moreover, the presence of T allele in 665C/T MTHFR polymorphism was also associated with significantly increased risk of the development of BCC (OR = 2.094, p = 0.00068). Conclusions : Based on the results it was found that the presence of CT genotype in the polymorphism 665C/T and CC genotype in the polymorphism 1286A/C in the MTHFR gene is an additional risk factor for basal cell skin cancers in the Polish population.